2011
DOI: 10.1590/s1678-91992011000100004
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and biological evaluation of gyroxin isolated from Crotalus durissus terrificus venom

Abstract: Gyroxin, a thrombin-like enzyme isolated from Crotalus durissus terrificus venom and capable of converting fibrinogen into fibrin, presents coagulant and neurotoxic activities. The aim of the present study was to evaluate such coagulant and toxic properties. Gyroxin was isolated using only two chromatographic steps - namely gel filtration (Sephadex G-75) and affinity (Benzamidine Sepharose 6B) - resulting in a sample of high purity, as evaluated by RP-HPLC C2/C18 and electrophoretic analysis that showed a mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 40 publications
0
38
0
2
Order By: Relevance
“…At the time of use, the components were previously thawed, reconstituted, mixed, and applied according to the following protocol: The first bottle had fibrinogen obtained from buffalo blood (5 μl), the second contained calcium chloride (2 μl), and the last bottle had a thrombin-like fraction (1 μl), totaling 8 μl [16,[23][24][25][26].…”
Section: Fibrin Sealantmentioning
confidence: 99%
“…At the time of use, the components were previously thawed, reconstituted, mixed, and applied according to the following protocol: The first bottle had fibrinogen obtained from buffalo blood (5 μl), the second contained calcium chloride (2 μl), and the last bottle had a thrombin-like fraction (1 μl), totaling 8 μl [16,[23][24][25][26].…”
Section: Fibrin Sealantmentioning
confidence: 99%
“…8a, b). Several reports have demonstrated that SVSPs are resistant to heat and/or pH denaturation (Costa et al 2009;Barros et al 2011;Menaldo et al 2012). However, none of these studies has reported the full maintenance of the enzymatic activity after pre-treating the enzymes on extreme pH and temperature conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were reported for gyroxin from Crotalus durissus terrificus, which is partially and completely inhibited by Ba 2+ and Cu 2+ , respectively. Gyroxin has also undergone the influence of Mn 2+ , which was not tested for collinein-1 ( Barros et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] In contrast, the new heterologous fibrin sealant derived from Crotalus durissus terrificus snake venom contains a thrombin-like protein with an activity similar to other forms of thrombin but about 4000-fold more potent than human thrombin. [34][35] Therefore, our fibrin sealant is produced from buffalo fibrinogen, a species able to donate a large amount of blood-diminishing product costs. 36,37 Together, these findings led us to conclude that fibrin gel made from the venom of the rattlesnake seems to present adequate consistency and stability.…”
mentioning
confidence: 99%